Parasitic potential-host range of Cuscuta sp. and its impact on Allium cepa L. grown in Jaffna - Amirthaveni, V.; Pakeerathan, K.; Thirukkumaran, G.; Mikunthan, G. (Proceedings of the International Symposium on Agriculture and Environment, 2012)
Cuscuta sp. is a familiarized medicinal plant for centuries but at times it has been reported parasitizing economically important crops like onion (Allium cepa L.) and chilli (Capsicum annum L). Due to the risk posed by this holoparasitic weed on cultivated crops, a field based research study was carried out with the objective of measuring parasitic potentiality of Cuscuta sp. through identifying minimum length of infective unit as tendril and its host searching ability, estimating biomass loss of A. cepa and screening of host range with selected vegetable crops and medicinal plants. Treatments were set up to measure the parasitic potential of Cuscuta sp. on different ages of A. cepa at two weeks and four weeks. Results revealed that minimum of five cm long Cuscuta tendril have the capability to initiate infection. Its tendrils have the potential to grow towards its host, A. cepa up to 60 cm distance. Therefore, spacing between two adjacent A. cepa plots more than 60 cm can be practicable to reduce the spreading of Cuscuta sp. At the time of harvesting, biomass loss of leaves and bulbs in two and four weeks old parasitized A. cepa were 58.4%, 14.5% and 89.1%, 46%, respectively. Dry weights of Cuscuta sp. were not significantly different at all the weeks. Number of leaves, shoot/root length ratio except number of bulbs, were significantly differed with age of A. cepa. Only two weeks old parasitized A. cepa yielded small size bulbs. Parasitic potential of Cuscuta sp. was not depend on the age of A. cepa. Results of host-parasite interactions showed that Brassica oleraceae and Raphanus sativus were the non-host crops of Cuscuta sp. Intercropping and crop rotation with non-host crops are the best alternatives in the crop fields suspected with infection of Cuscuta spp.